Toxic epidermal necrolysis‐like lupus. (1st October 2021) - Roberts, E. J.; Melchionda, V.; Saldanha, G.; Shaffu, S.; Royle, J.; Harman, K. E.
Summary: Toxic epidermal necrosis (TEN)‐like lupus is a rare condition characterized by epidermal loss and mucosal ulceration occurring in patients with acute severe flares of systemic lupus erythematosus. The clinical picture may mimic drug‐induced Stevens–Johnson syndrome/TEN; however, the absence of a suitable culprit drug, and the context of acute lupus point to the correct diagnosis. In a case series of three patients, further discriminating features included a slower onset of epidermal loss, more limited mucosal ulceration and a lack of ocular involvement when compared with drug‐induced TEN. Histology may show similar features, including basal layer vacuolation, apoptosis and full‐thickness epidermal necrosis. Patients with TEN‐like lupus may have additional features of lupus, and a lupus band on direct immunofluorescence. It is important to identify this condition correctly, so that these patients can be appropriately managed with early input from Rheumatologists and prompt treatment with high‐dose combined immunosuppressant therapy.